Evaluation of Knowledge, Awareness, and Practice of Adverse Drug Reactions at Aseer Central Hospital in Saudi Arabia - Abomughayedh, Ali Mohammed; Ali, Mohammed Salah (Journal of medical and pharmaceutical sciences, 2018)
The purpose of this research was to evaluate the knowledge, attitude, and practices (KAP) of the healthcare professionals (HCPs) about pharmacovigilance in Aseer Central Hospital in Saudi Arabia. A cross-sectional study was conducted using a pretested questionnaire. The questionnaire was designed to assess the KAP regarding pharmacovigilance procedure. The HCPs including physicians, nurses, and pharmacists, working in the Aseer Central Hospital participated in the research. Consents were first distributed to the HCPs and only those who gave their consents to were included in the research. The data were analyzed by using the Statistical Package for Social Sciences (SPSS) statistical software, version 22. The results showed that the majority of the healthcare professionals had good knowledge and attitude regarding pharmacovigilance and understand the necessity of reporting ADRs. However, the rate of reporting ADRs by the HCPs was remarkably low. There was a big gap between the ADRs experienced and ADRs reported by the participant HCPs. It was also found that there is a positive correlation between the training of pharmacovigilance and reporting ADRs reporting. It was realized that the majority of respondents agreed that reporting of ADRs was necessary and also were aware that pharmacovigilance should be taught in detail to healthcare professionals as that they have started to understand the importance of pharmacovigilance.